The elimination of iodine deficiency in the Czech Republic: the steps toward success - Zamrazil, V; Bilek, R; Cerovska, J; Delange, F (Thyroid, 2004)
The Czech Republic has a long history of iodine deficiency. Salt iodization was introduced in 1947, followed by a progressive correction of iodine deficiency. The present study reports the changes in the status of iodine nutrition and of thyroid function in the country from 1994 to 2002. The study included 29612 individuals, aged 0 to 98 years, including 5263 individuals randomly selected from the general population and 24349 individuals who attended the Institute of Endocrinology of Prague (hospital population). Urinary iodine was determined in all individuals. Measurements of serum thyrotropin (TSH), free thyroxine (FT4), free triiodothyronine (FT3), and thyroglobulin (Tg), were taken in 8544 to 19060 individuals. The iodine content of table salt was measured in 1130 samples. The median urinary iodine in the general and hospital populations were not significantly different. They progressively increased with time, starting from values indicating mild iodine deficiency (88-95 microg/L) prior to 1997, reaching the critical threshold of 100 microg/L in 1998, and optimal values between 120-140 microg/L since 2000. There was only a low and not significant positive correlation between the iodine content of salt and the urinary iodine. In contrast, urinary iodine showed marked seasonal changes, with the highest values during winter, when livestock were supplemented by mineral tablets containing iodine. Variables exploring thyroid function were all situated within the normal range in adults but another study (results not reported) has shown the persistence of slightly elevated TSH in neonates. The correction of iodine deficiency was not accompanied by unfavorable side effects. In conclusion, the Czech Republic has achieved sustainable elimination of iodine deficiency. Salt iodization has been a determining, but not the only, factor responsible for the success. Iodine supplementation of livestock and increased consumption of milk rich in iodine have probably played a determining role. Neonatal thyroid screening could constitute the major monitoring tool in order to insure sustainable elimination of iodine deficiency in the Czech Republic.
Keywords: nutriční stav; Humans; lidé středního věku; dítě; Child; jod; Female; Aged; dospělí; testy funkce štítné žlázy; senioři; lidé; Iodine; Nutritional Status; věkové rozložení; karenční nemoci; Adult; ženské pohlaví; Male; Middle Aged; Thyroid Function Tests; Czech Republic; Aged, 80 and over; Age Distribution; senioři nad 80 let; Česká republika; mužské pohlaví; Deficiency Diseases